Laïcité et faits religieux : conduire des débats avec les élèves, quels dispositifs ? - Nathalie Panissal; Hubert Strouk (Éducation et Socialisation)
The reactivation of the “religious fact” questions the teachers on their professional posture.: The analyses developed here correspond to questionings of trainers of teachers in charge of these questions. Situations of ordinary class with conferences and debates, discussed during the time on the birthday of the law of 1905 that has separated Churches from the State, are analyzed in order to be used as track with the initial training of the teachers. After having presented the scenarios of teaching and debates, we have studied the recorded corpora. The analyses led in terms of knowledge construction show that the reasons to be knowledge miss. The place reserved for the debate is thus extremely reduced. We discuss the interest of the preparatory phase to the debate and propose didactic tracks taking support on the inquiry approach.